NORWID’S CONCEPT OF LITERARY ORIGINALITY FROM THE PERSPECTIVE OF THE HISTORY OF POETICS - Stanisz, Marek (Colloquia Litteraria, 2018)
Norwid’s concept of Literary Originality in the Light of the History of Poetics The article presents Norwid’s concept of literary originality with reference to selected terms from the European theory of poetry. Norwid’s reflections about writing function predominantly within the confines of his philosophical concepts, which were mostly inspired by the philosophy of Plato and Christian thought and were related to his vision of God, the world, man, and artist. One can discover, however, a rich set of terms coming from traditional poetics in the works of the author of Quidam. Norwid’s thinking about originality is firmly rooted in tradition and links diverse inspirations and threads in a distinctive way. As such it shows telling paradoxes by containing unequivocal objection to imitating nature and exemplary works. At the same time, it underscores Norwid’s reliance on the old masters, advocates for the freedom and authenticity of artists, and highlights the role of the form in the creative process. While not dismissing the contradictory categories of ‘obscurity’ and fragmentariness, Norwid also pays attention to the value of artistic perfection. His concepts do not form a closed system of aesthetic views. Instead, they constitute an elastic catalogue of indications whose employment requires combined work of the imagination, intellect, and emotions as well as the alertness of one’s conscience and spiritual energy. Norwid believed that the primary duty of art was expressing the truth about the world.